The Role of the Independent Board of commissioners, Ownership, and Accountant Reputation on Social Disclosure: Case of Emerging Market - Hadi, Nor; Citradewi, Adelina; Ekaningrum, Ifada Retno; Triyani, Agus; Setyahuni, Suhita Whini (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
This study aimed to examine the effect of an independent board of commissioners, public accountant reputation, and public ownership proportion on social disclosure which is the purpose of the agency and legitimacy theory testing. It was carried out on the energy, manufacturing, and basic material companies listed on the Indonesian stock exchange in 2021. The sample of this study were 55 companies selected using a purposive random sampling technique. Sample were selected based on the criteria of CSR reporting availability. The ordinary least square was used to test the hypotheses. The testing result showed that public accountants and the proportion of share ownership by the public have a significant effect on social disclosure. This is due to the existence of public accountants and diversified ownership by the public increasing the supervision; as there is a quality assurance and the involvement of several parties in supervision. However, this research proved that the independent board of commissioners does not have a significant effect on social disclosure. This is because, in developing countries such as Indonesia, the role and function as well as compromising attitudes towards CEOs often take place. The distinction of this research showed that problems of agency and legitimacy theory often takes place due to permissiveness, politeness, and reluctance culture which extends to professional work matters. This study has limitations in variable measurement. Therefore, further studies should measure other variables related to the effectiveness of monitoring